PENERAPAN PENCAHAYAAN BUATAN SEBAGAI COMMERCIAL LIGHTING PADA KIOS BATIK PASAR KLEWER SURAKARTA - Huda Sahidah Faqih; Talitha Sandra Ayu; Valencia Audrey Santoso Budiman; Silfia Mona Aryani (Universitas Katolik Soegijapranata, 2025)
Artificial lighting plays a crucial role in product display, including for goods sold in traditional markets such as Klewer Market, Solo, renowned for its batik. This article aims to describe the artificial lighting system applied by batik vendors at Klewer Market. The research was conducted by observing the interior elements, including wall and ceiling conditions, and furniture, as well as measuring the lighting quality using a spectrometer at four kiosks. The results of these observations and measurements were analysed in accordance with recommended standards and theories related to lighting for commercial buildings. Observations revealed a lack of attention to the type and direction of lighting, as well as the lighting fixtures that should support the commercial function of market stalls. Measurements indicated that lighting in these stalls did not meet standards in terms of brightness and color rendering, and the use of white lights did not create a positive atmosphere in the store. It is recommended that stall owners pay more attention to lighting to ensure appropriate brightness, color rendering, color temperature, and lighting direction, which is expected to increase sales. The main issue identified is the low lighting quality in terms of brightness and color accuracy, which reduces the visual appeal of batik products. Practically, vendors can enhance product perception and attractiveness by adopting lighting with a color rendering index (CRI) of and correlated color temperature (CCT) between 3500 – 4000 K.